2014
DOI: 10.1111/pbr.12161
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci with main and epistatic effects for plant architecture traits in Upland cotton (Gossypium hirsutum L.)

Abstract: Plant architecture is important for cotton cultivation and breeding. In this study, two mapping generations/populations F 2 and F 2:3 in Upland cotton (Gossypium hirsutum L.), derived from 'Baimian1' and TM-1, were used to identify quantitative trait loci (QTLs) for 10 plant architecture traits. A total of 55 main-effect QTLs (M-QTLs) were detected. Four common M-QTLs, qTFB-10(F 2 /F 2:3 ) for total fruit branches, qFBL-26b(F 2 )/qFBL-26(F 2:3 ) for fruit branch length, qFBA-5(F 2 /F 2:3 ) for fruit branch ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Different strategies have been implemented through quantitative genetics models, quantitative trait loci (QTL) or mutation-QTL experiments (Mackay, 2014), but there is still no consensus on its importance. For plants, depending on the population and trait considered, some studies have shown that epistasis can significantly contribute to total genetic variance, for example, in maize (Dudley and Johnson, 2009), rice (Luo et al, 2009) or cotton (Li et al, 2014), while also improving the prediction accuracy (Dudley and Johnson, 2009;Hu et al, 2011). Meanwhile, other studies have shown that epistasis has a little impact regarding the genetic architecture of some traits in maize (Buckler et al, 2009) or in the prediction accuracy (Lorenzana and Bernardo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been implemented through quantitative genetics models, quantitative trait loci (QTL) or mutation-QTL experiments (Mackay, 2014), but there is still no consensus on its importance. For plants, depending on the population and trait considered, some studies have shown that epistasis can significantly contribute to total genetic variance, for example, in maize (Dudley and Johnson, 2009), rice (Luo et al, 2009) or cotton (Li et al, 2014), while also improving the prediction accuracy (Dudley and Johnson, 2009;Hu et al, 2011). Meanwhile, other studies have shown that epistasis has a little impact regarding the genetic architecture of some traits in maize (Buckler et al, 2009) or in the prediction accuracy (Lorenzana and Bernardo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Five significant main‐effect QTL for plant height were detected in Chr.2/Chr.1, Chr.14 and Chr.26, respectively, using RIL population (Li et al. ). The main‐effect QTL qPH‐D2‐1, qPH‐D6‐1, qPH‐D8‐2 and qPH‐A9‐1 were repeatedly detected across multiple environments using two immortalized populations of ‘CRI12’ × ‘J8891’ in G. hirsutum (Liu et al.…”
mentioning
confidence: 99%
“…Subsequently, several intraspecific genetic linkage maps were constructed for G. hirsutum (Lin et al 2009;Ulloa and Meredith 2000;Ulloa et al 2002Ulloa et al , 2005Zhang et al 2005Zhang et al , 2009, which contain 73-604 loci. Using these maps, the precise locations of many QTLs have been determined Guo et al 2006;Li et al 2014;Liu et al 2012;Ning et al 2014;Paterson et al 2003;Qin et al 2008Qin et al , 2009Shao et al 2014;Shen et al 2005Shen et al , 2007Sun et al 2012;Ulloa and Meredith 2000;Ulloa et al 2005;Wang et al 2006Wang et al , 2007Wu et al 2009;Zhang et al 2005Zhang et al , 2009Zhang et al , 2010Zhang et al , 2012a. For fiber quality, for example, Qin et al (2009) discovered eight QTLs for fiber strength (FS), micronaire (MIC) and fiber elongation (FE) simultaneously in two populations.…”
Section: Introductionmentioning
confidence: 99%
“…QTL mapping is increasingly used to explore the role of epistasis in the genetic basis of complex quantitative traits Mohan et al 2009). In cotton, QTL mapping analysis of epistatic effects has only been performed to examine a few plant architectural traits in intraspecific populations (Wang et al 2006;Li et al 2014). Wang et al (2006) identified three epistatic QTLs for plant height (PH), three for fruit branch length (FBL) and three for fruit branch number (FBN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation